Marxist thought in South Asia - Plys, Kristin; Priyansh; Goonewardena, Kanishka (Political power and social theory ;, 2023)
Marxism is not just a Euro-American preoccupation. It has had vibrant articulations around the world, particularly in Latin America, Africa, the Caribbean, and amongst Black diasporas. But South Asia has been relatively neglected in efforts to register the revolutionary theoretical traditions of the Global South. Reinvigorating the study of Marxism within the South Asian context, this volume of Political Power and Social Theory highlights lesser-known thinkers to unsettle the propensity within the Marxist cannon to disproportionately fixate on white male theorists. Forging an anti-imperialist Marxism through dialectical and historical approaches, chapters demonstrate how the South Asian facet of this revolutionary tradition can contribute to and even reenergize global Marxist theory.